2019
DOI: 10.1038/s41598-019-49661-5
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to anticoagulant rodenticides in Martinique could lead to inefficient rodent control in a context of endemic leptospirosis

Abstract: Leptospirosis is a re-emergent worldwide zoonosis. It is endemic in Martinique where transmission conditions are favourable. Humans are usually infected through contact with water contaminated with urine of rodents. Recent human leptospirosis outbreaks in Martinique require today effective rodent management to prevent leptospirosis transmission. Nowadays, use of anticoagulant rodenticides (AR) is the main method implemented to control rodent populations. Nevertheless, intensive use of these AR has selected wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…To explore the relationship between the known resistance mutations and the interspecific amino acid variations in desert rodents, we compared their positions referring to the Norway rat VKORC1 protein sequence and the 3D model. Previous studies have reported 29 sites with intraspecific VKORC1 amino acid changes (designated as capital letters and the position in the protein sequence) in common commensal rodents 2, 3, 15, 50–60, 64, 65 . The sites include 7 sites (E37, R58, W59, L124, L128, Y139, S149) in M. musculus , 15 sites (A21, A26, R33, R35, Y39, G46, S56, F63, E67, L120, I123, L128, Y139, A140 and E155) in R. norvegicus and 15 sites (A21, Y25, A26, H28, R35, E37, R40, A41, R58, R61, H68, L76, A115, Y129 and Y139) in R. rattus 2, 3, 15, 50–60, 64, 65 .…”
Section: Resultsmentioning
confidence: 99%
“…To explore the relationship between the known resistance mutations and the interspecific amino acid variations in desert rodents, we compared their positions referring to the Norway rat VKORC1 protein sequence and the 3D model. Previous studies have reported 29 sites with intraspecific VKORC1 amino acid changes (designated as capital letters and the position in the protein sequence) in common commensal rodents 2, 3, 15, 50–60, 64, 65 . The sites include 7 sites (E37, R58, W59, L124, L128, Y139, S149) in M. musculus , 15 sites (A21, A26, R33, R35, Y39, G46, S56, F63, E67, L120, I123, L128, Y139, A140 and E155) in R. norvegicus and 15 sites (A21, Y25, A26, H28, R35, E37, R40, A41, R58, R61, H68, L76, A115, Y129 and Y139) in R. rattus 2, 3, 15, 50–60, 64, 65 .…”
Section: Resultsmentioning
confidence: 99%
“…pour le bacille de la peste [Rahelinirina et al, 2021], les rickettsies du typhus murin [Rickettsia typhi : Rakotonanahary et al, 2017] ou les spirochètes de la leptospirose [Leptospira spp. : Marquez et al, 2019]). Mais des résistances à ces rodenticides apparaissent ensuite (Ratnadass et Deguine, 2021).…”
Section: Rodenticidesunclassified
“…In 60's; the first resistant rodent population has been described (21). To deal with the emergence of resistant rodent populations resulting from the use of these first generation of anticoagulant rodenticides (FGAR) (warfarin, diphacinone, chlorophacinone) a second generation of anticoagulant rodenticides (SGAR) has been developed (22)(23)(24). Second generation molecules (bromadiolone, brodifacoum, dicoumarol, difenacoum, difethialone.…”
Section: Use Of Anticoagulant Rodenticidesmentioning
confidence: 99%
“…The risk of a pesticide used to control target species by causing their death is to select living target species that are less or not sensitive to this pesticide, the latter specimens are said “resistant.” In 60's; the first resistant rodent population has been described ( 21 ). To deal with the emergence of resistant rodent populations resulting from the use of these first generation of anticoagulant rodenticides (FGAR) (warfarin, diphacinone, chlorophacinone) a second generation of anticoagulant rodenticides (SGAR) has been developed ( 22 24 ). Second generation molecules (bromadiolone, brodifacoum, dicoumarol, difenacoum, difethialone…) are more efficient against resistant rodents and effective at a lower dose.…”
Section: Anticoagulant Rodenticides Use and Propertiesmentioning
confidence: 99%